2016
DOI: 10.1088/1742-6596/671/1/012041
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Boric Acid on Volatile Products of Thermooxidative Degradation of Epoxy Polymers

Abstract: Abstract. The polymeric materials are characterized by high flammability. The use of flame retardants in order to reduce the flammability of polymers can lead to the formation of toxic gaseous products under fire conditions. In this work we studied the effect of boric acid on the volatile products of thermooxidative degradation of epoxy polymers. The comparative investigations were carried out on the samples of the unfilled epoxy resin and epoxy resin filled with a boric acid at percentage 10 wt. %. The analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…The samples exhibited two steps of weight loss. The first step, in the temperature range of 100–250 °C, was due to the thermal decomposition of PFR, first thermal dehydration of H 3 BO 3 , and second thermal dehydration of the latter [ 29 , 44 ]. The second step of weight loss appeared in the temperature range of 300–550 °C, due to the thermal decomposition of polymer matrix [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples exhibited two steps of weight loss. The first step, in the temperature range of 100–250 °C, was due to the thermal decomposition of PFR, first thermal dehydration of H 3 BO 3 , and second thermal dehydration of the latter [ 29 , 44 ]. The second step of weight loss appeared in the temperature range of 300–550 °C, due to the thermal decomposition of polymer matrix [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…These compounds improve the flame resistance of the polymers by acting in the gas and the condensed phases. They decompose endothermically, reducing the temperature of the system and producing water that can dilute flammable gases that result from the pyrolysis process [ 29 ]. In the condensed phase, they improve the formation and stabilization of a protective char layer on the polymer surface [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nazarenko et al have indicated that the addition of metal nanofillers such as aluminium to epoxy resin improves the thermal stability of the composite. [ 30 ] Because of the high thermal conductivity of the Ni nanofillers, the epoxy‐Ni nanocomposites are less effected by the thermal stress, compared to base epoxy resin. Also, the addition of Ni nanofillers enhances the electrical conductivity along with thermal conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…It completed at approximately 600 C. Consequently, BA lost all its water, and it was entirely transformed to boron oxide (B 2 O 3 ). 103,104 In addition, the interaction between components of the flame retardant IFR2.5BA-MMT (APP/BA/PER/MMT: 16.25/2.5/6.25/2) is clearly seen in Figure 3.…”
Section: Thermogravimetric Analysis (Tg/dtg) Of Pp and Its Compositesmentioning
confidence: 97%